Evaluation of the Abdala Vaccine: Antibody and Cellular Response to the RBD Domain of SARS-CoV-2 - Lorenzo Islas-Vazquez; Yan Carlos Alvarado-Alvarado; Marisa Cruz-Aguilar; Henry Velazquez-Soto; Eduardo Villalobos-Gonzalez; Gloria Ornelas-Hall; Sonia Mayra Perez-Tapia; Maria C. Jimenez-Martinez (Vaccines, 2023)
Abdala is a recently released RBD protein subunit vaccine against SARS-CoV-2. A few countries, including Mexico, have adopted Abdala as a booster dose in their COVID-19 vaccination schemes. Despite that, most of the Mexican population has received full-scheme vaccination with platforms other than Abdala; little is known regarding Abdala’s immunological features, such as its antibody production and T- and B-cell-specific response induction. This work aimed to study antibody production and the adaptive cellular response in the Mexican population that received the Abdala vaccine as a booster. We recruited 25 volunteers and evaluated their RBD-specific antibody production, T- and B-cell-activating profiles, and cytokine production. Our results showed that the Abdala vaccine increases the concentration of RBD IgG-specific antibodies. Regarding the cellular response, after challenging peripheral blood cultures with RBD, the plasmablast (CD19+CD27+CD38High) and transitional B-cell (CD19+CD21+CD38High) percentages increased significantly, while T cells showed an increased activated phenotype (CD3+CD4+CD25+CD69+ and CD3+CD4+CD25+HLA-DR+). Also, IL-2 and IFN-γ increased significantly in the supernatant of the RBD-stimulated cells. Our results suggest that Abdala vaccination, used as a booster, evokes antibody production and the activation of previously generated memory against the SARS-CoV-2 RBD domain.